Helminth parasites of Australasian monotremes and marsupials - Spratt, David M.; Beveridge, Ian (Zootaxa, 2016)
This work includes all published records, to April 2015, of the helminths occurring in Australasian monotremes and marsupials, with due regard for synonymy and an attempt to include life history studies, pathological observations and epidemiology. It also contains all unpublished records known to us and referrable, by accession numbers, to curated collections in Australia and overseas. Information is presented by host family, genus, species, sub-species or chromosome race and includes the names of all host species from which no parasites have been recorded. Most records pertain to free-living and wild animals; where they do not, they have been annotated appropriately. Unpublished information known to the authors has been included in annotations to entries, where appropriate. Parasites are arranged as follows: Trematoda, Cestoda, Nematoda, Acanthocephala, and their systematic position is indicated by abbreviations placed before the name. The authority for each parasite record is given after the author’s name, as a number in parentheses, and this refers to the numbered (1-664) list of references. A parasite-host list is presented alphabetically, irrespective of taxonomic affiliation together with the host species in which they are known to occur. Hosts are arranged initially by family and alphabetically within each family.